2019
DOI: 10.1155/2019/2462561
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Korea Red Ginseng on Inflammatory Cytokines and Apoptosis in Rat Model with Chronic Nonbacterial Prostatitis

Abstract: Chronic prostatitis typically occurs in aging men, and its symptoms include frequent and painful urination. In recent study, several studies have shown that Korean red ginseng (KRG) can be used in the prevention and treatment of various diseases. The objective of this study is to investigate whether KRG can play a role in repressing the development of chronic nonbacterial prostatitis (CNP) in male Wistar rats. To induce CNP, rats were castrated and beta-estradiol (0.25 mg/kg) was subcutaneously (s.c.) injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
(23 reference statements)
1
12
0
Order By: Relevance
“…TNF-α and IL-1β activation in the gut wall is associated with visceral pain in IBS [ 31 , [33] , [34] , [35] ]. Consistent with the previous report that RG suppresses IL-1β and NF-κB activation [ 36 ], RG treatment in our study significantly inhibited IL-1β expression in the colon. It also suppressed TNF-α expression, similar to that observed in the group treated with the anti-inflammatory SSZ compound.…”
Section: Discussionsupporting
confidence: 93%
“…TNF-α and IL-1β activation in the gut wall is associated with visceral pain in IBS [ 31 , [33] , [34] , [35] ]. Consistent with the previous report that RG suppresses IL-1β and NF-κB activation [ 36 ], RG treatment in our study significantly inhibited IL-1β expression in the colon. It also suppressed TNF-α expression, similar to that observed in the group treated with the anti-inflammatory SSZ compound.…”
Section: Discussionsupporting
confidence: 93%
“…Modern pharmacological studies have found that red ginseng contains ginsenosides or active components of ginsenosides, and animal experiments have shown that it can inhibit the expression of TNF-α, IL-1β, IL-6, and COX-2 in patients with CP/CPPS. [32] Moreover, Qian-Yu decoction is a traditional Chinese medicinal recipe. [33] The combined administration of three extracts, i.e.…”
Section: Tcm Can Affect Immune-mediated Inflammatory Factors To Reduc...mentioning
confidence: 99%
“…KRG is known to possess various biological and immunological activities including anti-inflammatory, anti-oxidative, and anti-tumorigenic properties [ 13 , 14 , 15 ]. Ginsenosides, the primary active constituents of ginseng, are saponins with steroid-like hydrophobic backbones connected to sugar moieties.…”
Section: Discussionmentioning
confidence: 99%
“…Heat-processing Panax ginseng Meyer converts ginsenoside compounds within the root to yield Korean Red ginseng (KRG). Since red ginseng has higher biological effects and fewer side effects than fresh ginseng, KRG is commonly used in traditional medicine throughout East Asia for its immunomodulatory, anti-allergic, anti-inflammatory, anti-oxidative, and anti-tumorigenic properties [ 13 , 14 , 15 ]. Various ginsenosides regulate inflammatory reactions through the regulation of cytokine, chemokine, and cyclooxygenase-2 production [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%